Impetus for Action: A Cultural Analysis of Justice and Organizational Citizenship Behavior in Chinese Society - Farh, Jiing-Lih; Earley, P. Christopher; Lin, Shu-Chi (Administrative Science Quarterly, 1997)
Jiing-Lih Farh, P. Christopher Earley, Shu-Chi Lin, Impetus for Action: A Cultural Analysis of Justice and Organizational Citizenship Behavior in Chinese Society, Administrative Science Quarterly, Vol. 42, No. 3 (Sep., 1997), pp. 421-444